Ancient literacies : the culture of reading in Greece and Rome - Johnson, William A. (William Allen), 1956-; Parker, Holt N. (Oxford University Press, 2009)
Recent advances in cognitive psychology, socio-linguistics, and socio-anthropology are revolutionizing our understanding of literacy. However, this research has made only minimal inroads among classicists. In turn, historians of literacy continue to rely on outdated work by classicists (mostly from the 1960s and 1970s) and have little access to the current reexamination of the ancient evidence. This timely volume seeks to formulate interesting new ways of conceiving the entire concept of literacy in the ancient world, as text-oriented events embedded in particular socio-cultural contexts. This book rethinks from the ground up how students of classical antiquity might best approach the question of literacy in the past, and how that investigation might materially intersect with changes in the way that literacy is now viewed in other disciplines. The result provides new ways of thinking about specific elements of “literacy” in antiquity, such as the nature of personal libraries, or what it means to be a bookseller in antiquity; new constructionist questions, such as what constitutes reading communities and how they fashion themselves; new takes on the public sphere, such as how literacy intersects with commercialism, or with the use of public spaces, or with the construction of civic identity; new essentialist questions, such as what do “book” and “reading” signify in antiquity, why literate cultures develop, or why literate cultures matter.